Dubliners - Joyce, James, 1882-1941.; Johnson, Jeri. (New York : Oxford University Press, 2000)
Presents James Joyce's vignettes of everyday life in Dublin, Ireland at the turn of the century; and includes an introduction, a chronology, explanatory notes, and other reference tools.
Includes bibliographical references (p. [xlvii]-liii).
Young Adult
Keywords: City and town life -- Fiction; City and town life -- Fiction; Short stories; Dublin (Ireland) -- Social life and customs -- Fiction; Dublin (Ireland) -- Social life and customs -- Fiction